BATIK LABAKO: MEMBANGUN KECINTAAN TERHADAP BUDAYA MELALUI PEMBELAJARAN IPS KONTEKSTUAL - Hartono, Budi Hartono; Wardana, I Gede Wayan Wisnu Wardana (Universitas Islam Zainul Hasan Genggong, 2025)
As a typical cultural heritage of Jember Regency, Labako batik has local values such as environmental wisdom, hard work, and cultural identity. This study examines the potential use of Batik Labako values as an alternative learning resource for Social Studies learning in elementary schools. The purpose of this research is to find out how teachers in primary schools in Jember can use these values as learning resources, so as to improve the relevance and quality of social studies learning in primary schools. The themes related to the research problem were analyzed through a qualitative approach and literature review research type. Data were collected from journals as secondary sources. The thematic method was used to analyze the educational values of Batik Labako and its application model in social studies learning. The results showed that primary school teachers in Jember can utilize the values by incorporating them into thematic materials, creating culture-based learning models, and visiting batik santras. This application improves students' understanding of social studies materials and instills respect for local culture.